Development of a Web-Based E-Administration System for the Indralaya Ogan Ilir Police Department Utilizing the System Development Life Cycle (SDLC) Approach - Devi Udariansyah; Asta Sapriyogi (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Information technology advancement has transformed administrative processes across government institutions, particularly within law enforcement agencies. This research examines the development of a web-based E-Administration application at the Indralaya Ogan Ilir Police Resort, designed to improve efficiency, accuracy, and accessibility in administrative services. The application development follows the System Development Life Cycle (SDLC) methodology, providing a structured approach through planning, analysis, design, implementation, testing, and maintenance phases. The study seeks to optimize administrative workflows, minimize paperwork dependency, and strengthen data security protocols. Results demonstrate that system implementation delivers more effective and efficient administrative processes, enhancing service quality and operational performance within the police department. Future research should focus on integrating advanced security measures and expanding functionality to accommodate broader administrative requirements.